Cesarean Section without Urethral Catheterization: A Randomized Control Trial - Acharya, S; Uprety, DK; Pokharel, HP; Amatya, R; Rai, R (Kathmandu University Medical Journal, 2013)
Background Urethral catheterization is done as a routine procedure in cesarean section. It is associated with high incidence of urinary tract infections, discomfort, delayed ambulation and longer hospital stay. Objective To determine the feasibility and safety of cesarean section without urethral catheterization. Methods A prospective, randomized controlled trial was carried out from April 2008 to March 2009, in the Department of Obstetrics and Gynecology, B. P. Koirala Institute of Health Sciences. Among 150 patients who had undergone cesarean section 75 were catheterized and 75 were uncatheterized. Results First void discomfort was significantly associated with the use of indwelling catheter (OR 6.95, CI 95 %, 3.74 to 12.95; P< 0.001).Significant number of patients with indwelling catheter had signs and symptoms of urinary tract infection (OR 6,CI 95%, 2.59 to 13. 86; P < 0.001). Positive urinalysis for urinary tract infection was high in catheterized group (P <0.001). Hospital stay was shorter in patients without catheter (p < 0.05). None of the patients had bladder injury. There were no significant differences in duration of surgery and ambulation time between two groups of patients. Conclusions Cesarean section can be done safely without urethral catheterization with reduced morbidities. Kathmandu University Medical Journal | Vol.10 | No. 2 | Issue 38 | Apr – June 2012 | Page 18-22 DOI: http://dx.doi.org/10.3126/kumj.v10i2.7337